End hunger, achieve food security and improved nutrition and promote sustainable agriculture - Mollier, Ludovic; Seyler, Frédérique; Chotte, Jean-Luc; Ringler, Claudia (International Council for Science, 2017)
This brief description of sdg 2 – the ‘entry level goal’ for this assessment – is followed by an overview of interactions at goal level between sdg 2 and the other 16 sdgs. Taking into account all the underlying targets of this entry goal, a set of key interactions is then identified between the sdg 2 targets and those of other sdgs, focusing on interactions with high magnitude or strong impacts based on available scientific literature and expert knowledge. The typology and seven-point scale for characterising the range of positive and negative interactions described in the opening chapter to this report is used to assess the selected target-level interactions and the context in which they typically occur. Illustrative examples from different world regions show how these linkages manifest in practice. Policy options that can enhance positive and reduce negative interactions between now and 2030, and beyond are also described. The chapter concludes with a list of key knowledge gaps related to the interactions studied.